ASSESSING THE IMPACT OF EARNINGS QUALITY AND FINANCIAL FLEXIBILITY ON FIRM VALUE: INSTITUTIONAL OWNERSHIP AS A MODERATING FACTOR - Ni Putu Anindya Sarasija Prameswari; Kadek Marlina Nalarreason (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
The aim of this study was to empirically investigate the impact of financial flexibility and profits quality on business value with institutional ownership serving as a moderating variable. Since a company's worth increases with its cash management, this study examines cash holdings to gauge financial flexibility. All non-cyclical consumer sector businesses listed on the Indonesia Stock Exchange (IDX) in 2021–2023 make up the study's population. Purposive sampling combined with non-probability sampling was the sample strategy employed in this study, which yielded 67 firms. Using the SPSS software, this research method is called Moderated Regression Analysis (MRA). The findings demonstrated that firm value is unaffected by earnings quality. Because the market reaction is usually negative, low earnings quality cannot raise firm value. Firm value is positively and significantly impacted by financial flexibility. The correlation between business value and earnings quality is strengthened by institutional ownership. The association between corporate value and financial flexibility is weakened by institutional ownership. The corporation has not engaged in strategic decision-making with business-savvy institutional investors Because they think the business's cash reserves are susceptible to misuse by corporate management, investors do not include them in their investment.